FAKTOR YANG MEMPENGARUHI KESEJAHTERAAN MASYRAKAT DI DESA CERMIN ALAM, KAB TEBO, PROVINSI JAMBI - Meli Susanti; Novera Martilova (CV. Adiba Aisha Amira, 2023)
The background of this thesis is the level of community welfare in the village of Cermin Alam, VII Koto Ilir, Tebo District, Jambi Province where there are still many people who are classified as having a low level of welfare due to the fact that their income level is still relatively low, there are still many unemployed people and still low levels of income level of education. The purpose of this research is to get results and to find out and analyze how much influence income levels, unemployment, and education levels have on the level of community welfare, where this research has used quantitative research by distributing questionnaires and getting answers from the people who are the samples of this research. The results of this study indicate that the level of welfare is related to the factors that influence the level of social welfare in the form of income, education, employment/unemployment, number of family members and age. From these factors, this study only takes 3 factors to obtain the results, namely: income, unemployment, and education where the results of the Variable Income, Unemployment, and Education Level have a significant effect on the level of community welfare in the village where the research was conducted.